Economic Analysis of Hybrid Renewable Energy Systems with V2G Integration Considering Battery Life - Baloglu, Ulas Baran; Demir, Yakup (Elsevier Science Bv, 2017)
Hybrid renewable energy systems considered as candidate solutions for environmental problems. Solar energy and wind energy are important components of these systems, but both of them cause fluctuations in the grid. Batteries of Electric Vehicles (EVs) can be connected to the grid to create an ancillary resource. These systems known as Vehicle to Grid (V2G) and they could be the most suitable solution to the fluctuation problems of renewable resources. In this paper, economic analysis of V2G is investigated from various perspectives. The findings of this study indicate that battery aging costs of a V2G system can be minimized with an intelligent energy management system, and these systems are both economically and environmentally better alternatives to fossil-fuelled generators. (C) 2016 The Authors. Published by Elsevier Ltd.
3rd International Conference on Energy and Environment Research (ICEER) -- SEP 07-11, 2016 -- Barcelona, SPAIN
Keywords: electric vehicles; hybrid renewable energy systems; smart grid; V2G